Financing Cancer Care in Bangladesh: An Alternative Route - Hamid, Syed Abdul; Talukder, Md. Habibullah; Tasnim, Afrida; Kabir, Muhammad Ihsan- Ul- (International Journal of Social and Administrative Sciences, 2021)
The enormous financial burden of cancer treatment due to lack of any structured financing mechanism results in catastrophic health expenditures as well as impoverishment to many households in Bangladesh. This study attempts to design an alternative mechanism for providing financial protection to cancer patients for receiving necessary procedures (e.g., screening, chemotherapy, radiotherapy, and surgical procedures) based on imposing some levy on mobile phone subscribers using primary and secondary data. The study finds that a monthly fixed levy of BDT 21.5 (USD 0.26) on each active mobile phone subscriber can provide annual financial protection of BDT500,000 (USD 5,882) to each of 60,000 cancer patients currently seeking treatment from domestic facilities. A fixed levy is always regressive and therefore burdensome for poverty-stricken subscribers. Allocation of the monthly fixed levy on the mobile phone call rate can generate similar worth more equitably. Successful transformation of this idea into action may increase access to cancer care and reduce financial burden as well as disease burden in Bangladesh.